A comparative legal study of the dilution of registered trade marks in selected jurisdictions to further the development of the remedy in South African law - Van der Walt, Elizabeth Margaretha (Stellenbosch : Stellenbosch University, 2012)
Thesis (LLD)--University of Stellenbosch, 2005.